HOW TO EVALUATE THE EFFECTIVENESS OF TEACHER TALK - Glover, Philip (International Online Journal of Education and Teaching, 2018)
Talk is a key component of teaching and learning and teacher talk is an important part of how a teacher teaches. This paper discusses principles and approaches for analysing teacher talk in classroom interaction in order to investigate its effectiveness. The paper presents four reasons for analysing teacher talk: the role of interaction in the management of learning, the analysable, interpretable and explainable nature of discourse, the value of analysing effective teaching and the existence of categories of teacher talk that support the investigation of effective teaching. These categories are based on a framework of Elicitations, Responses and Descriptions from Mercer (1995). The paper also looks at issues of reliability, validity and generalisability of findings. The paper concludes that a focus on categories of teacher talk can support academic research, for the supervision and evaluation of teachers by managers, as well as for self-development purposes by teachers themselves.